1999
DOI: 10.1144/gsl.sp.1999.153.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Angola: source rock control for Lower Congo Coastal and Kwanza Basin petroleum systems

Abstract: The purpose of this paper is to provide an overview of petroleum occurrence and provenance for the 1000 km West African Atlantic Margin from Cabinda to mid-Angola. Over this margin the Lower Congo Coastal and Kwanza provinces cumulatively account for reserves of c. 6 gigabarrels oil recoverable (GBOR). These are dominantly reservoired in Pinda carbonate traps of the former basin. However, with production from a range of aggradational wedge, carbonate platform and pre-salt reservoirs, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 6 publications
0
49
0
1
Order By: Relevance
“…On the other hand, the presence of medium-and heavy-paraffins in the pyrolysates are directly linked to the concentration of terrestrial OM in the kerogen, and probably to depositional environment conditions allowing optimal OM preservation. However, this may not explain the dominance of C 14þ compounds in other lacustrine formations, such as the GRS one and the Bucomazi Formation (Angola) where there is a lack of terrestrial OM (Burwood, 1999;Ruble et al, 2001).…”
Section: Organic Matter Sources and Maturity Of Oil-shalesmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, the presence of medium-and heavy-paraffins in the pyrolysates are directly linked to the concentration of terrestrial OM in the kerogen, and probably to depositional environment conditions allowing optimal OM preservation. However, this may not explain the dominance of C 14þ compounds in other lacustrine formations, such as the GRS one and the Bucomazi Formation (Angola) where there is a lack of terrestrial OM (Burwood, 1999;Ruble et al, 2001).…”
Section: Organic Matter Sources and Maturity Of Oil-shalesmentioning
confidence: 97%
“…n-alkanes with a number of carbon > 14, also called n-C 14þ [Behar et al, 2010;Burwood, 1999;Derenne et al, 1994;Ruble et al, 2001;Tissot and Welte, 1984]). However, past studies of lacustrine source-rocks showed that a variation of medium-heavy paraffins concentration (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). This is not surprising given the thick sequences of source rocks in this area, including presalt (Early Cretaceous syn-rift lacustrine) and postsalt (mid Cretaceous to Tertiary postrift marine) sources (Burwood, 1999). The oils are classified as being of marine, lacustrine or "mixed" source, on the basis of their C 26 /C 25 tricyclic terpane and hopane/sterane ratios ( Fig.…”
Section: Methylhopanes As a Correlation Tool: Offshore West Africamentioning
confidence: 97%
“…6. Classification of the offshore West African oils using a cross-plot of the C 26 /C 25 tricyclic terpane and hopane/sterane ratios (Burwood, 1999;Schiefelbein et al, 1999). The hopane/sterane ratio uses Ts, Tm, 28,30-bisnorhopane, C 29 ␣␤, C 29 ␤␣, C 30 ␣␤, C 30 ␤␣, and C 31 to C 35 ␣␤ 22Sϩ22R hopanes, and C 27 to C 30 ␣␤␤ 20Sϩ20R steranes.…”
Section: Methylhopanes In Oils and Source Rocksmentioning
confidence: 99%